“Estética y política: ¿discursos visuales?. Reflexiones en torno a la imagen y a los imaginarios sociales en Cristianismo y Revolución (1966-1971)” - Moira Cristiá (Centre de Recherches sur les Mondes Américains, 2008)
This article aims to analyse the political usage of image in an Argentinean magazine published between 1966 and 1971. Cristianismo y Revolución reflects social and political tensions during the “Argentinean Revolution”, especially in Catholicism. Although a significant analysis of this journal has already been done, this paper deals with a group of questions related to its visual dimension. After exploring its eclectic symbolic universe, some hypothesis about the usage of image in the process of political communication are outlined. Three outstanding aspects are examined in the body of this article in order to think theoretically the relations between aesthetics and politics, as a result of a further interest in the social imaginary of the peronist left.